Kinetic And Equilibrium Studies On The Adsorption Of Pb2+ And Zn2+ From Aqueous Solution Using Coco-Peat By Batch Experiment - Kukuh Jalu Waskita; Augustus C. Resurreccion; Wawan Budianta (Journal of Applied Geology, 2015)
The presence of heavy metals in surface water, which is common in mining area pose harmful effect to human health and the environment. Recently, cocopeat has been studied as an effective sorbent material for removing heavy metals from wastewater. In this study, kinetic was done by analyzing the distribution of the heavy metal in sorbent material and liquid phase after mixing 50 mg/L solution of lead (Pb2+) and zinc (Zn2+)in single solute system with 0.1 g of coco-peat, that were consequently shaken at 5, 10, 15, 30, 60, 120, 180 and 360 minutes. To determine the equilibrium adsorption isotherm for each heavy metal, the solutions of 10, 20, 30,40 and 50 mg/L of Pb2+ and Zn2+ were prepared separately. Two different pH levels (natural pH, and pH 4) were setto describe the sorption behavior of Pb2+ and Zn2+ of each heavy metal.Using data from batch experiments, appropriate kinetic (time dependency) and equilibrium (isotherm) models were fitted on the sorbent material and liquid phase concentrations to determine adsorption parameters. Pseudo second-order kinetic model fitted well to the kinetic data due to chemisorption that happened during experiments. In other hand, Langmuir model fitted well to the equilibrium, this indicates that the sorption of lead and zinc on coco peat is monolayer and that the adsorbent’s surface is homogenous. The increase of heavy metals adsorption following the increase of pH might be due to negative charge of coco peat surface. Pb2+ adsorbed more than Zn2+ because ion with high hydration enthalpy will have smaller amount of ion adsorbed. The hydration enthalpies for Pb2+ and Zn2+ are 23 kJ/kg and 113 kJ/kg, receptively. Considering all the factors that we have discussed, cocopeat has high efficiency to remove the heavy metals from wastewater. Keywords: Coco-peat, adsorption, batch experiment, kinetic, equilibrium.